Analysis of Students Difficulties in Learning Listening Comprehension of Eleventh Grade Students at Senior High School 9 Jambi - Rosyada, Amrina; Suyadi, Suyadi; Kurniati, Erisa (Universitas Batanghari Jambi, 2024)
The process of learning that involves listening comprehension aids pupils in comprehending the subject or lesson being covered. The goal of this study is to learn more about the challenges that children have with reading comprehension. based on the observations made by the researcher during fieldwork (PPL). When listening to audio content, some pupils experience difficulty. This research use qualitative method and the data was gathered by questionnaire. According to the analysis of students difficulties listening comprehension, listening is an extremely challenging skill for language learners. The factors that affected their listening were the phsyical environment, the listener factor, and the listening content. Therefore, the English Education main issues with students accent, pronunciation, speech rate, vocabulary and diverse speaker accents were combined with a lack of focus and poor recording quality. Understanding students challenges can motivate effective learning strategies to help students improve their listening skills. It also suggested remedies to the challenges, such as the teacher adapting and improving listening material, activating students vocabulary, providing a diversity of accents while practicing listening in a language laboratory, and improving their pronunciation through instruction from native speakers. The study findings may be valuable to people who are interested the topic.Keyword : Listening, Difficulties